Systematic review of the effectiveness and tolerability of hyaluronic acid for acute and chronic wounds / Atikah Shaharudin - Atikah, Shaharudin (2016)
Hyaluronic Acid (HA) and its derivatives are commonly used for acute and chronic wounds, but evidence of their effectiveness remains unclear. The aim of the study was to evaluate the effectiveness of HA (or its derivatives) for promoting healing in acute and chronic wounds through a systematic review of the available evidence. The Cochrane Central Register of Controlled Trials and relevant databases were searched. Drugs companies and experts in wounds were also contacted. Randomised controlled trials of HA (or its derivatives) compared with control were eligible for inclusion. Ten randomised controlled trials involving 992 participants with acute and chronic wounds were included in the review. The research evidence was weak with poor reporting in many trials. The evidence does not provide strong support for the beneficial effects of HA (or its derivatives) towards improvement of chronic wounds even though there is some evidences that they were effective for reducing pain intensity for mixed arterial and venous ulcers [MD= -6.78 (95% CI: -11.10 to -2.46)]. Evidence to guide decisions regarding the use of HA (or its derivatives) to promote wound healing is still limited. More good quality randomised controlled trials are warranted.